Toxic gases adsorbed on graphene oxide with vacancy: a theoretical study - Salazar, Estuardo; Litchina, Gabriela; Goulart, Luiza; Rossato, Jussane (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
Emission of toluene and formaldehyde emission is related to several health problems, such as cancer, cardiovascular and respiratory diseases. Studies show the use of graphene oxide as a gas sensor. Therefore, the aim of this study is to investigate the electronic and structural properties of the interaction between graphene oxide with vacancy (GOV) and toluene and formaldehyde. In this study, the SIESTA code was used, which is based on the Density Functional Theory (DFT). The interaction between toluene and the GOV that presented the lowest binding energy (-0.86 eV) was the one in which toluene was planarly approximated by vacancy. The interaction between formaldehyde and the GOV that presented a lower binding energy (-0.90 eV) is the one in which formaldehyde is planarly approximated by hydroxyl. For both cases, the electronic properties remained unchanged and the electronic density plots of charge are more concentrate on the nanostructure. All interactions occurred in a physical adsorption regime; thus, a possible application for GOV would be as a filter for industry vents.